2021
DOI: 10.1590/2177-9465-ean-2020-0249
|View full text |Cite
|
Sign up to set email alerts
|

Adesão à consulta puerperal: facilitadores e barreiras

Abstract: Resumo Objetivos identificar a prevalência de adesão e não adesão à consulta puerperal, assim como facilitadores e barreiras, entre puérperas assistidas em um hospital de ensino. Método estudo de coorte prospectivo, realizado com 121 puérperas, no período de agosto a dezembro de 2019, nas dependências de um hospital de ensino do interior de Minas Gerais. Resultados a prevalência de adesão à consulta puerperal foi de 34,7%. Observou-se, como facilitador, o acolhimento da equipe durante o pré-natal e/ou parto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 24 publications
(63 reference statements)
0
3
0
7
Order By: Relevance
“…When the reasons for nonadherence are investigated, there are reasons for forgetfulness, complications with the NB, transportation difficulties, and distance between home and health unit. 34 As associated factors, it is found that puerperal consultation is related to lower income and schooling, as well as not being addressed/valued during prenatal consultations. 35…”
Section: Discussionmentioning
confidence: 99%
“…When the reasons for nonadherence are investigated, there are reasons for forgetfulness, complications with the NB, transportation difficulties, and distance between home and health unit. 34 As associated factors, it is found that puerperal consultation is related to lower income and schooling, as well as not being addressed/valued during prenatal consultations. 35…”
Section: Discussionmentioning
confidence: 99%
“…Atenção puerperal durante pandemia por COVID- 19 Novakowiski RDF, Baggio MA, Zilly A a gente não tem essa informação [...] a gente precisa realmente fazer busca para conhecer essas pacientes (G1).…”
Section: [] Em Foz Do Iguaçu a Gente Não Recebe Dnv Quem Recebe A Dnv...unclassified
“…Os profissionais informaram que anterior à pandemia já havia elevado número de usuários vinculados ao serviço, área de cobertura extensa e déficit de recursos humanos. Não obstante isto, o afastamento de profissionais pertencentes ao grupo de risco ou à infecção por COVID- 19 Outro fator que sobrecarrega a APS do município é a localização geográfica -região de tríplice fronteira. Residentes em países vizinhos, principalmente, de nacionalidade paraguaia ou brasileiros que residem no Paraguai, os quais procuram por atendimento em saúde no Brasil, somando fatores de sobrecarga a um sistema já deficitário.…”
Section: [] Em Foz Do Iguaçu a Gente Não Recebe Dnv Quem Recebe A Dnv...unclassified
“…Therefore, to provide such relevant assistance, each Primary Care team member's continuing training and education plays an essential role in these individuals' follow-up success, ensuring both physical and emotional comfort and preventing complications for both the mother and the child 5, 6 . However, there are flaws in the quality of the attention provided by these professionals during the first week after birth, with very low or even non-existent home visit indicators [7][8][9][10] . In this context, Community Health Workers (CHW) tend to adopt their judgment to define risks, without the proper orientation of the nursing professional, who is responsible for leading the nursing team and has the attribution of supervising the CHW 11, 12 .…”
Section: Profile and Knowledge Of Brazilian Amazon Primary Health Car...mentioning
confidence: 99%